Calcium aluminate-calcium oxide composite material, method for preparing same, and use thereof
Patent Information
- Application Number
- CN202611465320.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-20
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]本申请提供了一种铝酸钙-氧化钙复合料及其制备方法和应用,以解决目前苛化渣处理技术普遍存在能耗偏高、产物活性不足、铝钙资源无法同步高效回收、固废资源化程度低的问题
1、本申请实施例提供的铝酸钙-氧化钙复合料,该铝酸钙-氧化钙复合料中Na2O残留量低于0.5%,有效避免了该复合料在回用于氧化铝生产过程中钠元素的循环富集,保障系统运行稳定性;同时,实现了CaO与Al2O3的协同高效回收,提升了资源综合利用效率。
Smart Images

Figure CN122977419A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of resource utilization of solid waste from the alumina industry and preparation of inorganic non-metallic materials, and particularly to a calcium aluminate-calcium oxide composite material, its preparation method and application. Background Technology
[0002] The Bayer process is currently the mainstream technology in alumina production. During its salt desalination and causticization process, a large amount of industrial solid waste, causticization slag, is generated as a byproduct. This type of causticization slag has a complex mineral composition, mainly containing calcium carbonate, calcium aluminate hexahydrate, calcium hydroxide, and trace amounts of sodium salts. It is rich in valuable components such as calcium and aluminum, and has extremely high potential for resource recovery and utilization.
[0003] Currently, the conventional treatment methods for alumina causticizing slag in the industry are relatively crude, mostly involving direct landfilling or sale for cement production. Some processes employ traditional high-temperature calcination to recover calcium oxide products. However, current treatment processes have many inherent defects. Crude landfilling not only occupies land resources but also easily leads to environmental problems such as alkaline leakage and soil and water pollution. Cement resource utilization can only achieve low-value disposal, and the valuable aluminum components inside the slag cannot be effectively recovered, resulting in extremely low resource utilization. At the same time, traditional high-temperature calcination processes are energy-intensive and have crude reaction conditions, producing calcium oxide products with poor activity, which cannot meet the application requirements of high-end resource utilization products. Furthermore, the calcination process generally suffers from incomplete decomposition of calcium carbonate, easy agglomeration and growth of calcium aluminate crystals, and continuous enrichment of alkaline components in the system, making it impossible to achieve simultaneous and efficient recovery of alumina and calcium oxide. Ultimately, this leads to incomplete resource utilization of causticizing slag and low added value, resulting in a significant waste of valuable resources and hindering the green and circular development of solid waste in the alumina industry.
[0004] Currently, some research focuses on optimizing the structure of caustic slag calcination equipment, only improving the calcination device without in-depth research on the caustic slag calcination process system and the technology for the synergistic recovery and utilization of valuable calcium and aluminum resources. Furthermore, it still uses the traditional high-temperature calcination mode, resulting in high energy consumption and poor resource recovery. Some existing technologies use microwave-coupled high-temperature calcination to treat silicon-aluminum waste slag, recovering aluminum components through high-temperature activation and acid leaching separation. However, this process has limited adaptability and cannot specifically address the industry pain points of simultaneous calcium and aluminum activation, product activity control, and alkali enrichment elimination in Bayer process caustic slag, making it difficult to achieve high-value, integrated resource utilization of caustic slag.
[0005] In view of this, it is necessary to design a calcium aluminate-calcium oxide composite material, its preparation method and application, in order to solve the above problems. Summary of the Invention
[0006] This application provides a calcium aluminate-calcium oxide composite material, its preparation method, and its application, in order to solve the problems of high energy consumption, insufficient product activity, inability to simultaneously and efficiently recover aluminum and calcium resources, and low degree of solid waste resource utilization in current caustic slag treatment technologies.
[0007] In a first aspect, this application provides a calcium aluminate-calcium oxide composite material, wherein, by mass percentage, the composition of the calcium aluminate-calcium oxide composite material includes CaO: ≥82%, 3CaO·Al2O3: ≥10%, Na2O: <0.5%, and the remainder being impurities; The activity of CaO in the calcium aluminate-calcium oxide composite is >380 mL.
[0008] Secondly, this application provides a method for preparing the above-mentioned calcium aluminate-calcium oxide composite material, comprising the following steps: The causticizing slag is subjected to dealkali treatment to obtain dealkali-reduced slag; The dealkali-removed residue is mixed with a composite modifier to obtain a calcined raw material; The calcined raw material is subjected to microwave step-calcination treatment to obtain calcined clinker; and, The calcined clinker was subjected to rapid cooling treatment to obtain a calcium aluminate-calcium oxide composite material; The composite modifier includes lithium source, lanthanum source, cerium source and boron source.
[0009] In some embodiments, the mass ratio of the causticizing slag to the composite modifier is 100:(0.4~1.3); and / or, In the composite modifier, the mass ratio of the lithium source, the lanthanum source, the cerium source, and the boron source is (2~6):(1~3):(0.5~2):(0.5~2).
[0010] In some embodiments, the lithium source includes LiF; and / or, The lanthanum source includes La(NO3)3·6H2O; and / or, The cerium source includes CeO2; and / or, The boron source includes Na2B4O7·10H2O.
[0011] In some embodiments, the microwave stepped calcination process includes sequentially subjecting the calcined raw material to low-temperature dehydration and activation treatment, medium-temperature decomposition treatment, and heat preservation and homogenization treatment.
[0012] In some embodiments, the microwave power of the low-temperature dehydration activation treatment is 6kW~8kW; and / or, The homogenization temperature for the low-temperature dehydration and activation treatment is 450℃~550℃; and / or, The homogenization time for the low-temperature dehydration and activation treatment is 8 min to 12 min; and / or, The microwave power for the intermediate-temperature decomposition process is 10kW~12kW; and / or, The homogenization temperature of the mesophilic decomposition treatment is 780℃~850℃; and / or, The homogenization time for the mesophilic decomposition treatment is 20 min to 25 min; and / or, The microwave power for the heat preservation and homogenization treatment is 5kW~7kW; and / or, The homogenization temperature of the heat preservation treatment is 750℃~800℃; and / or, The homogenization time for the heat preservation treatment is 5 min to 8 min.
[0013] In some embodiments, the dealkali treatment includes the following steps: The causticized residue is mixed with water and stirred for the first time to obtain a solid-liquid mixture; The solid-liquid mixture is subjected to liquid-solid separation treatment to obtain a solid phase; and, The solid phase is dried to obtain the dealkali residue.
[0014] In some embodiments, the stirring temperature of the first stirrer is 80°C to 90°C; and / or, The stirring time for the first stirring is 0.1 h to 1 h; and / or, The solid-liquid ratio of the causticized slag to water is 1 g:(2~6) mL; and / or, The drying process is performed at a temperature of 100℃~105℃; and / or, The moisture content of the dealkali removal residue is <3% by mass percentage; and / or, The particle size of the dealkali-removing residue is ≤127μm.
[0015] In some embodiments, the rapid cooling process includes cooling the calcined clinker to ≤200°C at a cooling rate of 80°C / min to 180°C / min.
[0016] Thirdly, this application provides an application of the above-mentioned calcium aluminate-calcium oxide composite material, which is used in salt desalination and causticizing processes and deep desilication processes.
[0017] The technical solutions provided in this application have the following advantages compared with the prior art: 1. The calcium aluminate-calcium oxide composite material provided in this application embodiment has a Na2O residue of less than 0.5%, which effectively avoids the cyclic enrichment of sodium elements in the process of recycling the composite material in the production of alumina and ensures the stability of system operation; at the same time, it realizes the synergistic and efficient recovery of CaO and Al2O3, and improves the comprehensive utilization efficiency of resources.
[0018] 2. This application also provides a method for preparing the above-mentioned calcium aluminate-calcium oxide composite material. This involves dealkalizing the causticizing slag, introducing a composite modifier containing lithium, lanthanum, cerium, and boron sources, followed by microwave stepped calcination and rapid cooling to finally obtain the calcium aluminate-calcium oxide composite material. This method has the following beneficial effects: First, dealkalizing the causticizing slag effectively reduces the content of soluble sodium salts; second, during the subsequent microwave stepped calcination process, the dealkalized slag and the composite modifier synergistically exert an in-situ solidification effect, further inhibiting the cyclic enrichment of Na2O in the alumina production system. Secondly, in the composite modifier, the lithium and boron sources work synergistically to significantly reduce the activation energy of CaCO3 decomposition and promote efficient low-temperature reactions; the lanthanum and cerium sources work synergistically to effectively inhibit the sintering and grain coarsening of 3CaO·Al2O3 at high temperatures, stabilize its active crystal form, refine the product grains, and prevent calcium aluminate from passivating or agglomerating due to overheating; at the same time, multiple modifying components work together to promote the in-situ solidification of Na2O, reduce Na2O residue in the product, meet the requirements for reuse, and achieve efficient synergistic recovery of CaO and Al2O3.
[0019] 3. The application of the calcium aluminate-calcium oxide composite material provided in this application embodiment is that the calcium aluminate-calcium oxide composite material can be directly reused in the desalination causticization or deep desilication process of alumina production; in the causticization process, the causticization efficiency is >96%, and the Al2O3 recovery rate is >92%; in the desilication process, the desilication index is >0.95, and the SiO2 in the refined solution is <0.08 g / L. Compared with the limitation of the prior art that only recovers CaO, this application achieves an Al2O3 recovery rate of >92% and a lime utilization rate of >95%, and constructs a closed-loop circulation system of "causticization slag → composite modification → microwave calcination → reuse → new causticization slag → recalcination". Attached Figure Description
[0020] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.
[0021] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0022] Figure 1 A process flow diagram of a calcium aluminate-calcium oxide composite material provided in Embodiment 1 of this application is shown. Detailed Implementation
[0023] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0024] Various embodiments of this application may exist in the form of a range. It should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a rigid limitation on the scope of this application. Therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. In addition, whenever a numerical range is indicated in this application, it means including any referenced number (fraction or integer) within the indicated range. Unless otherwise specified, all raw materials, reagents, instruments, and equipment used in this application can be purchased commercially or prepared by existing methods. In this application, unless otherwise stated, directional terms such as "upper" and "lower" specifically refer to the drawing directions in the accompanying drawings. In addition, in this application, the terms "comprising," "including," etc., mean "including but not limited to." In this application, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, without necessarily requiring or implying any actual relationship or order between these entities or operations. In this application, "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A alone, A and B simultaneously, or B alone. A and B can be singular or plural. In this application, "at least one" means one or more, and "more than one" means two or more. "At least one," "at least one of the following," or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c," or "at least one of a, b, and c," can both represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can each be single or multiple.
[0025] This application provides a calcium aluminate-calcium oxide composite material, which includes CaO, 3CaO·Al2O3 and trace impurities; by mass percentage, CaO: ≥82%, 3CaO·Al2O3: ≥10%, Na2O: <0.5%, and the remainder being impurities.
[0026] Preferably, the calcium aluminate-calcium oxide composite material comprises, by mass percentage: CaO: 82%~88%, 3CaO·Al2O3: 10%~25%, Na2O: 0.1%~0.5%, with the remainder being impurities; In the calcium aluminate-calcium oxide composite, the activity of CaO is >380 mL.
[0027] The calcium aluminate-calcium oxide composite material provided in this application has a Na2O residue of less than 0.5%, which effectively avoids the enrichment of sodium in the alumina production system during the recycling process and ensures the stability of system operation. At the same time, it realizes the synergistic and efficient recovery of CaO and Al2O3, and improves the comprehensive utilization efficiency of resources.
[0028] like Figure 1 As shown, based on a general inventive concept, this application provides a method for preparing the above-mentioned calcium aluminate-calcium oxide composite material, including the following steps: Step 1: Dealkali treatment is performed on the causticizing slag to obtain dealkali-treated slag; Step 2: Mix the dealkali-removed residue with a composite modifier to obtain calcined raw material; Step 3: Perform microwave stepped calcination on the calcined raw material to obtain calcined clinker; Step 4: Rapidly cool the calcined clinker to obtain the calcium aluminate-calcium oxide composite material; The composite modifier includes lithium source, lanthanum source, cerium source and boron source.
[0029] This application provides a method for preparing a calcium aluminate-calcium oxide composite material. The method involves dealkalizing the causticizing slag, introducing a composite modifier containing lithium, lanthanum, cerium, and boron sources, followed by microwave stepped calcination and rapid cooling to obtain the final calcium aluminate-calcium oxide composite material. This method offers the following advantages: First, dealkalizing the causticizing slag effectively reduces the content of soluble sodium salts. Second, during the subsequent microwave stepped calcination, the dealkalized slag and the composite modifier synergistically exert an in-situ solidification effect, further inhibiting the cyclic enrichment of Na2O in the alumina production system. Secondly, in the composite modifier, the lithium and boron sources work synergistically to significantly reduce the activation energy of CaCO3 decomposition and promote efficient low-temperature reactions; the lanthanum and cerium sources work synergistically to effectively inhibit the sintering and grain coarsening of 3CaO·Al2O3 at high temperatures, stabilize its active crystal form, refine the product grains, and prevent calcium aluminate from passivating or agglomerating due to overheating; at the same time, multiple modifying components work together to promote the in-situ solidification of Na2O, reduce Na2O residue in the product, meet the requirements for reuse, and achieve efficient synergistic recovery of CaO and Al2O3.
[0030] In this embodiment, the synergistic in-situ solidification effect of the dealkali slag and composite modifier is a key part of controlling the entry of alkali into alumina production in this technology. During the stepped microwave calcination process, the low-sodium dealkali slag after water washing pretreatment undergoes a synergistic in-situ solidification reaction with various composite modifiers such as LiF, lanthanum nitrate, nano-cerium dioxide, and sodium tetraborate decahydrate. First, in the low-temperature section, boron salt dehydration forms a boron-oxygen liquid phase capturing system to capture free sodium ions, while lithium fluoride promotes the decomposition of calcium carbonate and buffers the migration activity of sodium ions. Second, in the medium-temperature main calcination section, rare earth oxides are doped into the 3CaO·Al2O3 lattice, replacing some calcium ions with high-charge rare earth cations to form a multi-component sodium-calcium-aluminum rare earth solid solution, permanently locking sodium ions in the interstices of the crystal lattice. The heat preservation and homogenization section completes the crystal phase reconstruction, which, combined with subsequent rapid freezing at 80℃ / min~180℃ / min, stabilizes the lattice. At the same time, trace amounts of residual sodium ions generate a boron rare earth silicate passivation encapsulation phase. Because the dealkali residue provides abundant calcium aluminate lattice carriers, combined with composite modifiers, a triple sodium-fixing synergistic effect of "liquid phase capture - lattice doping - surface passivation" is achieved, controlling the soluble sodium oxide content in the clinker to below 0.5%. When the composite material is applied to the causticizing and deep desiliconization processes of alumina, the sodium ions solidified in the lattice are difficult to dissolve in Bayer's high-alkali mother liquor, significantly reducing the introduction of additional ineffective carbon and alkali, inhibiting the continuous enrichment of Na2O in the alumina recycling production system from the source, and avoiding a series of production problems such as excessive carbon and alkali in the mother liquor, increased evaporation and salt discharge load, and equipment scaling.
[0031] In the embodiments of this application, the caustic slag (dry basis) used, by mass percentage, comprises: 65%~70% CaCO3, 20%~23% 3CaO·Al2O3·6H2O, 3%~8% Ca(OH)2, 1%~3% Na2O, 1%~2% SiO2, and the remainder being impurities.
[0032] As an optional implementation, in this embodiment, the mass ratio of the causticizing slag to the composite modifier is 100:(0.4~1.3). It should be noted that all causticizing slag mentioned throughout this document is a dry basis after drying treatment.
[0033] For example, the mass ratio of the causticizing slag to the composite modifier can be selected as 100:0.4, 100:0.6, 100:0.8, 100:1, 100:1.2, or 100:1.3.
[0034] Preferably, the mass ratio of the causticizing slag to the composite modifier is 100:(0.8~1.0).
[0035] Thus, limiting the mass ratio of causticizing slag to composite modifier to 100:(0.4~1.3) balances both technical and economic efficiency with effective application. If the content of composite modifier is too high (i.e., the mass ratio of causticizing slag to composite modifier is less than 100:1.3), it will lead to an excessively high proportion of inert components such as rare earth oxides and boron salts in the finished product, diluting the effective phase content of free CaO and calcium aluminate, resulting in insufficient effective calcium source in the composite material, and a decrease in causticizing efficiency and lime utilization. Simultaneously, excessive borate will form too many glassy phase coatings during calcination, hindering the contact reaction between CaO, 3CaO·Al2O3, and the mother liquor, thus reducing the product's reactivity. Furthermore, excessive addition of rare earth and boron salts will significantly increase raw material costs, resulting in insufficient industrial economics. If the content of the composite modifier is too low (i.e., the mass ratio of causticizing slag to composite modifier is greater than 100:0.4), it will not provide enough rare earth doped cations and boron-oxygen liquid phase capture sites, significantly weakening the in-situ sodium fixation effect. The residual amount of soluble Na2O in the finished product will increase, and after reuse, it will easily cause continuous enrichment of carbon and alkali in the Bayer mother liquor, forcing an increase in the evaporation and salt removal load. Simultaneously, insufficient modifier will lead to a decrease in the decomposition and activation effect of calcium carbonate, resulting in coarse CaO grains after calcination, insufficient 3CaO·Al2O3 formation, and low crystallinity of the calcium aluminate phase, failing to meet the process requirements for deep desilication and efficient Al2O3 recovery. Therefore, considering all factors, this application controls the mass ratio of causticizing slag to composite modifier within the range of 100:(0.4~1.3).
[0036] As an optional implementation, in this embodiment of the application, the mass ratio of the lithium source, the lanthanum source, the cerium source and the boron source in the composite modifier is (2~6):(1~3):(0.5~2):(0.5~2).
[0037] For example, in the composite modifier, the mass ratio of the lithium source, the lanthanum source, the cerium source, and the boron source can be selected as 5:2:1:1, 4:2:1.5:1, 6:3:2:2, 3:1:0.5:0.5, or 5:3:1:1.5.
[0038] Preferably, in the composite modifier, the mass ratio of the lithium source, the lanthanum source, the cerium source and the boron source is (3~5):(1.5~2.5):(1~1.5):(1~1.5).
[0039] Thus, in the composite modifier, limiting the mass ratio of lithium source, lanthanum source, cerium source, and boron source to (2~6):(1~3):(0.5~2):(0.5~2) allows the four components to synergistically exert a triple in-situ sodium-fixing effect of liquid-phase capture, lattice doping, and surface passivation, simultaneously promoting the low-temperature decomposition of calcium carbonate and the efficient formation of calcium aluminate phase. This ensures that the Na2O content in the finished composite material is stably below 0.5%, the free CaO activity is >380mL, and the 3CaO·Al2O3 content is ≥10%, balancing deep desodium removal, maintaining product activity, and raw material economy. If the lithium source content is too high, it will lead to an increase in F in the system. - When the concentration of ineffective elements is too high, excessive fluorides react with calcium and aluminum during calcination to form a low-activity calcium fluoroaluminate inert phase, consuming effective CaO and calcium aluminate components and reducing the reactivity of the finished product; simultaneously, excessive Li + It will crowd out the interstitial spaces of calcium aluminate crystals, hindering the reaction of rare earth cations with Na. + The doping and solid solution actually weakens the in-situ sodium fixation effect, and excessive fluoride increases the cost of flue gas treatment and environmental protection. If the lithium source content is too low, it cannot effectively destroy the CaCO3 lattice, the reduction in the activation energy of calcium carbonate decomposition is limited, the decomposition temperature is too high, the decomposition is incomplete, and the content of free CaO in the finished product is insufficient; at the same time, Li + The buffering effect on sodium ion migration is weakened, and sodium salts are more likely to volatilize with the calcination flue gas and re-adhere to the material surface, leading to an increase in the residual soluble Na2O in the finished product, making it difficult to stably control it below 0.5%. Excessive lanthanum source content will cause excessive enrichment of rare earth oxides in the system, diluting the proportion of effective phases such as CaO and 3CaO·Al2O3, reducing the causticizing and desilication capabilities per unit mass of the composite material; simultaneously, excessive La... 3+ This will cause excessive distortion of the calcium aluminate lattice, forming a highly stable rare-earth calcium-aluminum solid solution, which in turn inhibits the dissolution reaction of calcium aluminate in the mother liquor, weakening the desilication and alumina recovery effects. Furthermore, lanthanum salts are expensive, and excessive addition significantly increases raw material costs, reducing industrial economics. If the lanthanum source content is too low, the supply of rare-earth doping cations is insufficient, failing to form enough stable doping sites in the 3CaO·Al2O3 lattice, leading to Na… + It is difficult to effectively lock it into the interstitial crystal lattice, significantly weakening the in-situ sodium fixation effect and increasing the residual amount of soluble Na2O in the finished product. This can easily lead to carbon and alkali enrichment in the Bayer mother liquor after reuse. Simultaneously, the crystal phase stability decreases, and CaO grains tend to grow during calcination, reducing product activity. Excessive cerium source content can cause nano-CeO2 particles to agglomerate, failing to disperse uniformly in the calcium-aluminum matrix, resulting in localized rare earth enrichment and a reduction in active sites. Furthermore, excessive CeO2... 4+High-melting-point cerium-calcium oxides are generated during calcination, hindering the decomposition of calcium carbonate and the formation of calcium aluminate, reducing the effective phase content of the finished product. Furthermore, nano-cerium oxide is expensive, making excessive use uneconomical. If the cerium source content is too low, the rare earth synergistic catalytic activation effect is insufficient, failing to effectively lower the calcination reaction energy barrier, resulting in a slower calcium carbonate decomposition rate and lower calcium aluminate formation. Simultaneously, Ce... 4+ To Na + The auxiliary lattice support effect is weakened, the synergistic sodium fixation effect with the lanthanum source decreases, the stability of the finished product Na2O control deteriorates, and the refining effect of active grains is correspondingly weakened. If the boron source content is too high, a large amount of glassy borate liquid phase will be formed during calcination, excessively coating CaO and 3CaO·Al2O3 active grains, hindering the contact reaction between the finished product and the mother liquor, resulting in a decrease in the reaction activity of the composite material and a slowdown in the causticization and desilication rates; at the same time, excessive borate will introduce additional Na2O. + This can partially offset the in-situ sodium fixation effect, and excessive boron components entering the circulating mother liquor may gradually accumulate, interfering with the alumina fractionation process. If the boron source content is too low, sufficient boron-oxygen liquid phase trapping sites cannot be formed in the low-temperature section, leading to the free Na+... + It is difficult to pre-adsorb and fix the sodium salt, and a large amount of sodium salt still exists in a free state in the mid-temperature range, which increases the subsequent rare earth lattice sodium fixation load, resulting in a high residual Na2O in the final product. At the same time, the liquid phase fluxing and dispersion effect is insufficient, the reaction uniformity between the modifier and the calcium-aluminum matrix decreases, and both in-situ sodium fixation and activation effects are affected. Therefore, taking all factors into consideration, in the composite modifier, this application controls the mass ratio of lithium source, lanthanum source, cerium source and boron source in the range of (2~6):(1~3):(0.5~2):(0.5~2).
[0040] As an optional implementation, in this embodiment of the application, the lithium source includes LiF; the lanthanum source includes La(NO3)3·6H2O; the cerium source includes CeO2; the particle size of CeO2 is 20nm~80nm; and the boron source includes Na2B4O7·10H2O.
[0041] As an optional implementation, in this embodiment of the application, the microwave stepped calcination treatment can be carried out using a 2.45GHz continuous microwave reactor.
[0042] As is well known, traditional rotary kilns and vertical calcination rely on surface radiation combined with heat conduction for heating. Heat gradually penetrates from the outer layer of material particles inward, resulting in a significant internal and external temperature gradient. This leads to overheating and grain coarsening in the outer layer, while insufficient heating in the inner layer results in incomplete reactions. The reaction kinetic energy is solely provided by high-temperature heat, lacking molecular-level activation effects. 2.45GHz microwave heating, however, is dielectric volume coupling heating, exhibiting thermal effects combined with non-thermal polarization synergistic effects, fundamentally different from ordinary heating principles. Traditional heating transfers heat from the outside of the material inward, creating a significant temperature gradient, easily leading to localized overheating and incomplete internal reactions, relying solely on high-temperature heat energy to drive mineral transformation. In contrast, 2.45GHz microwaves use an alternating electric field to induce high-frequency vibrations of polar molecules within the material, generating heat and achieving synchronous and uniform overall heating. Simultaneously, the electric field polarization weakens mineral chemical bonds, reducing the apparent activation energy of the mineral transformation reaction. Therefore, by introducing a composite modifier into the causticized slag after dealkalization treatment and combining it with microwave treatment, multiple synergistic modification effects can be achieved: reducing reaction activation energy, stabilizing calcium aluminate crystals, enhancing product activity, and controlling alkali residue. Microwave heating with no temperature difference throughout the entire process avoids the defects of local overheating and uneven reaction in traditional calcination, enabling the decomposition of calcium carbonate and the synthesis of calcium aluminate at a lower calcination temperature, significantly reducing the overall energy consumption of the process. At the same time, the synergistic effect of microwave volumetric heat effect and electric field polarization can enhance the in-situ lattice solidification reaction of boron and rare earth modified components with sodium salt and calcium aluminum matrix, stably generating fine and highly active 3CaO·Al2O3 crystal phase, inhibiting grain coarsening during sintering, which not only greatly improves the reactivity of free CaO, but also stably controls the soluble Na2O in the clinker to below 0.5%, simultaneously optimizing product quality and production process efficiency.
[0043] As an optional implementation, in this embodiment of the application, the microwave stepped calcination treatment includes sequentially performing low-temperature dehydration activation treatment, medium-temperature decomposition treatment, and heat preservation homogenization treatment on the calcined raw materials.
[0044] In this way, by controlling the temperature in stages, dehydration, decomposition and homogenization can be achieved in stages: ensuring that CaCO3 is fully decomposed, effectively inhibiting the over-burning and passivation of 3CaO·Al2O3, refining the grain size and improving the activity of the product, and finally obtaining high-quality calcined clinker.
[0045] As an optional implementation, in this embodiment of the application, the microwave power of the low-temperature dehydration activation treatment is 6kW~8kW; the homogenization temperature of the low-temperature dehydration activation treatment is 450℃~550℃; and the homogenization time of the low-temperature dehydration activation treatment is 8min~12min.
[0046] For example, the microwave power of the low-temperature dehydration activation treatment can be selected as 6kW, 7kW, or 8kW.
[0047] Preferably, the microwave power of the low-temperature dehydration activation treatment is 6.5kW~7.5kW.
[0048] For example, the homogenization temperature of the low-temperature dehydration activation treatment can be selected as 450℃, 500℃, or 550℃.
[0049] Preferably, the homogenization temperature of the low-temperature dehydration activation treatment is 480℃~520℃.
[0050] For example, the homogenization time of the low-temperature dehydration activation treatment can be selected as 8 min, 9 min, 10 min, 11 min, or 12 min.
[0051] Preferably, the homogenization time for the low-temperature dehydration activation treatment is 9 min to 11 min.
[0052] Thus, the purpose of the low-temperature dehydration and activation treatment stage is to remove free water and crystal water from the calcined raw materials. At the same time, the dehydration of boron salts forms a boron-oxygen liquid phase capture system to capture free sodium ions, and lithium fluoride initially activates the calcium carbonate lattice and weakens the Ca-O chemical bond, laying the foundation for subsequent deep decomposition in the medium temperature range and in-situ sodium fixation reaction.
[0053] As an optional implementation, in this embodiment of the application, the microwave power of the intermediate-temperature decomposition process is 10kW~12kW; the homogenization temperature of the intermediate-temperature decomposition process is 780℃~850℃; and the homogenization time of the intermediate-temperature decomposition process is 20min~25min.
[0054] For example, the microwave power of the intermediate temperature decomposition process can be selected as 10kW, 11kW, or 12kW.
[0055] Preferably, the microwave power of the intermediate-temperature decomposition process is 10.5kW to 11.5kW.
[0056] For example, the homogenization temperature of the intermediate-temperature decomposition process can be selected as 780℃, 800℃, 820℃, 840℃, or 850℃.
[0057] Preferably, the homogenization temperature of the intermediate-temperature decomposition treatment is 800℃~830℃.
[0058] For example, the homogenization time of the intermediate temperature decomposition treatment can be selected as 20 min, 22 min, 24 min, or 25 min.
[0059] Preferably, the homogenization time for the intermediate-temperature decomposition treatment is 21 min to 23 min.
[0060] Thus, the purpose of the intermediate-temperature decomposition treatment is to achieve the complete decomposition of CaCO3 and generate nanocrystalline 3CaO·Al2O3 material in situ; at the same time, rare earth oxides are doped into the calcium aluminate lattice at high temperature, stabilizing and locking the pre-captured sodium ions in the interstitial spaces, completing the core in-situ sodium fixation reaction. The temperature in this stage is controlled at 780℃~850℃, which reduces energy consumption by more than 30% compared with traditional rotary kiln calcination (>1000℃), significantly reducing production costs.
[0061] As an optional implementation, in this embodiment of the application, the microwave power of the heat preservation and homogenization treatment is 5kW~7kW; the heat homogenization temperature of the heat preservation and homogenization treatment is 750℃~800℃; and the heat homogenization time of the heat preservation and homogenization treatment is 5min~8min.
[0062] For example, the microwave power of the heat preservation and homogenization treatment can be selected as 5kW, 6kW, or 7kW.
[0063] Preferably, the microwave power of the heat preservation and homogenization treatment is 5.5kW to 6.5kW.
[0064] For example, the heat homogenization temperature of the heat preservation and homogenization treatment can be selected as 750℃, 760℃, 770℃, 780℃, or 800℃.
[0065] Preferably, the heat homogenization temperature of the heat preservation treatment is 760℃~780℃.
[0066] For example, the heat homogenization time of the heat preservation and homogenization treatment can be selected as 5 min, 6 min, 7 min, or 8 min.
[0067] Preferably, the heat homogenization time of the heat preservation treatment is 6 min to 7 min.
[0068] Thus, the heat preservation and homogenization treatment is to stabilize the crystal form of sodium rare earth doped 3CaO·Al2O3 and highly active free CaO multi-component solid solution, eliminate the internal thermal stress of the clinker after heating, uniformly refine the grains and avoid overheating and passivation, and ensure that the subsequent rapid cooling process can completely lock the highly active crystal phase structure.
[0069] In this embodiment, the heating rate of the microwave stepped calcination treatment is 80℃ / min to 120℃ / min. Utilizing the volumetric heating characteristics of microwaves, rapid stepped heating is achieved, avoiding the gradual growth of grains and decrease in activity during slow heating, while also preventing localized thermal stress cracking and boron salt liquid phase splashing and loss due to excessively rapid heating. This ensures precise control of the reaction window at each stage, ultimately yielding calcined clinker with uniform grains, excellent activity, and stable sodium residue.
[0070] As an optional implementation, in this embodiment of the application, the dealkali treatment includes the following steps: The causticized slag and water are placed in a reaction vessel, mixed, and stirred for the first time to obtain a solid-liquid mixture; The solid-liquid mixture is subjected to liquid-solid separation treatment to obtain a solid phase; The solid phase is dried to obtain the dealkali residue.
[0071] Thus, the dealkali treatment can pre-dissolve most of the soluble sodium salts in the causticizing slag, significantly reducing the background sodium content of the raw materials and alleviating the in-situ sodium fixation load of the subsequent composite modifier from the source. Without pre-dealkali treatment, the total sodium in the raw materials will be too high, exceeding the lattice capacity limit of the rare earth-boron modification system. Relying solely on calcination modification will not be able to control the finished Na2O content below 0.5%, which will easily lead to carbon-alkali enrichment in the alumina system after reuse. At the same time, removing soluble salts eliminates the sodium salt agglomeration and encapsulation effect, enabling the subsequent dry-based causticizing slag and composite modifier to achieve micron-level uniform mixing, improving the uniformity of boron salt sodium capture and rare earth lattice doping reaction during microwave calcination. In addition, water washing to remove soluble salts can prevent sodium salts from melting and agglomerating at high temperatures and adhering to the furnace cavity during the calcination stage, ensuring the continuous and stable operation of the three-stage microwave stepped calcination. This lays a prerequisite foundation for subsequent calcination and in-situ modification reactions in terms of sodium content, material mixing uniformity, and continuous equipment production.
[0072] As an optional implementation, in this embodiment of the application, in order to ensure thorough dealkali removal, the stirring temperature of the first stirrer is 80℃~90℃, the stirring time of the first stirrer is 0.1h~1h, and the stirring speed of the first stirrer is 200r / min~250r / min.
[0073] As an optional implementation, in this embodiment of the application, the solid-liquid ratio of the causticized slag to water is 1g:(2~6)mL.
[0074] Thus, by synergistically controlling the stirring temperature, stirring time, stirring rate, and solid-liquid ratio, efficient and complete dissolution of soluble sodium salts in causticizing slag can be achieved: a higher stirring temperature (80℃~90℃) can significantly improve the solubility and dissolution rate of sodium salts, accelerating the mass transfer of sodium salts from the solid phase to the liquid phase; a suitable stirring time and a stirring rate of 200r / min~250r / min ensure sufficient solid-liquid contact and complete dissolution of sodium salts, while avoiding excessive particle shearing and refinement that could affect subsequent liquid-solid separation; a solid-liquid ratio of 1g:(2~6)mL provides sufficient dissolution water, ensuring complete dissolution of soluble sodium salts without residue due to insufficient water, while also avoiding excessive water volume that could increase the load on subsequent liquid-solid separation and wastewater treatment. These three factors synergistically achieve an effective reduction in the background sodium content of the dealkali-removing slag, laying a low-sodium raw material foundation for subsequent in-situ sodium fixation with composite modifiers and microwave calcination.
[0075] As an optional implementation, in this embodiment of the application, the drying temperature is 100℃~105℃; The moisture content of the dealkali-removing residue is <3% by mass percentage; As an optional implementation, in this embodiment of the application, in order to ensure the uniformity of the composition of the dealkali slag and lay a good foundation for its subsequent calcination and modification treatment, the solid is dried and then ground to make the particle size of the dealkali slag ≤127μm.
[0076] As an optional implementation, in this embodiment of the application, the rapid cooling treatment includes: cooling the calcined clinker to ≤200°C at a cooling rate of 80°C / min to 180°C / min.
[0077] For example, the cooling rate during the rapid cooling process can be selected as 80℃ / min, 100℃ / min, 120℃ / min, 150℃ / min, or 180℃ / min.
[0078] Preferably, the rapid cooling rate is 110℃ / min to 130℃ / min.
[0079] Therefore, cooling the calcined clinker at a rate of 80℃ / min to 180℃ / min is to rapidly freeze the stable lattice of sodium rare earth-doped calcium aluminate and the fine, highly active free CaO grains formed at high temperatures. This prevents the crystal phase from recrystallizing, coarsening, and passivating during slow cooling, while also inhibiting the desorption and precipitation of sodium ions solidified in the interstitial spaces, which then revert to soluble sodium salts. This ensures the stable preservation of the clinker's high activity and low sodium soluble properties. If the cooling rate during rapid cooling is lower than 80℃ / min, the clinker will remain in the high-temperature zone for too long, causing CaO and 3CaO·Al2O3 grains to recrystallize, grow, and sinter, resulting in a decrease in the product's specific surface area and an activity level below 380mL. Simultaneously, the lattice will loosen, allowing the in-situ solidified sodium ions to precipitate from the interstitial spaces and reform soluble sodium salts. This increases the Na2O content in the finished product, which can easily lead to alkali enrichment in the Bayer system after reuse. If the cooling rate during rapid cooling exceeds 180℃ / min, the clinker particles will be subjected to excessive instantaneous thermal shock, generating a large amount of ultrafine dust and fly ash, resulting in a decrease in material yield and a surge in the load on the dust removal system. At the same time, rapid cooling causes the internal thermal stress of the clinker to concentrate, resulting in too many lattice defects and poor stability. Furthermore, it places excessive demands on the heat exchange capacity and industrial operation economy of the rapid cooling equipment, which is not conducive to continuous and stable production.
[0080] Based on a general inventive concept, this application provides an application of the above-mentioned calcium aluminate-calcium oxide composite material, which is applied to the salt desalination causticizing process and the deep desilication process.
[0081] This application provides an application of calcium aluminate-calcium oxide composite material. Specifically, it uses alumina desalination causticizing slag as raw material, adds a composite modifier containing lithium, lanthanum, cerium, and boron, and employs a three-stage microwave stepped calcination process to prepare a highly active calcium aluminate-calcium oxide composite material. This material is then reused in the desalination causticizing or deep desilication processes in alumina production, achieving high-value utilization of the causticizing slag and simultaneous and efficient recovery of CaO and Al2O3. Compared to the limitations of existing technologies that only recover CaO, this application achieves an Al2O3 recovery rate >92% and a lime utilization rate >95%, and constructs a closed-loop recycling system of "causticizing slag → composite modification → microwave calcination → reuse → new causticizing slag → recalcination," significantly improving resource utilization efficiency and process sustainability.
[0082] As an optional implementation, in this embodiment of the application, the method of applying the salt removal causticization process includes: The calcium aluminate-calcium oxide composite material, which has been ball-milled to a particle size of less than 53 μm, is mixed with the seed mother liquor at a CaO / Na2CO3 molar ratio of 1.05 to 1.15. The mixture is then reacted at 95°C to 105°C for 30 to 90 minutes. After the reaction is completed, the mixture is separated by sedimentation to obtain the causticizing liquid and residue.
[0083] Under these conditions, the causticization efficiency is >96% and the Al2O3 recovery rate is >92%.
[0084] As an optional implementation, in this embodiment of the application, the method of applying the calcium aluminate-calcium oxide composite material to a deep desilication process includes: The calcium aluminate-calcium oxide composite material, which has been ball-milled to a particle size of less than 53 μm, is mixed with crude liquid at a CaO / SiO2 molar ratio of 2.8 to 3.2, and then reacted at 100℃ to 110℃ for 60 min to 90 min. The reaction product is then separated by sedimentation to obtain a refined liquid.
[0085] This process can achieve a desilication index >0.95, a SiO2 content <0.08g / L in the semen, and simultaneous recovery of CaO and Al2O3.
[0086] The mechanism of action is as follows: at the causticizing temperature, 3CaO·Al2O3 in the composite material can be slowly hydrolyzed, releasing Ca(OH)2 to participate in the causticizing reaction, while simultaneously generating Al(OH)4. - Returning to the alumina production process, during the desilication process, 3CaO·Al2O3 directly reacts with SiO2 in the sodium aluminate solution to generate a stable hydrated garnet precipitate, thereby achieving deep desilication and simultaneous and efficient recovery of Al2O3 and CaO.
[0087] The present application is further illustrated below with reference to specific embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national standards. If no corresponding national standard exists, then generally accepted international standards, conventional conditions, or conditions recommended by the manufacturer are followed.
[0088] Example 1 Example 1 provides a method for preparing calcium aluminate-calcium oxide composite material, comprising the following steps: Step 1: Dealkali treatment is performed on the causticizing slag to obtain dealkali-treated slag; The dealkali removal process includes the following steps: The causticized slag and water were mixed in a reaction vessel at a solid-liquid ratio of 1g:5mL and stirred for the first time to obtain a solid-liquid mixture. The stirring temperature for the first stirring was 85℃, the stirring time for the first stirring was 35min, and the stirring speed for the first stirring was 200r / min. A solid-liquid mixture is subjected to liquid-solid separation treatment to obtain a solid phase (filter cake) and a filtrate; The solid material was successively dried and ground (ball milled) to obtain alkali-removing residue with a particle size ≤80μm; the moisture content of the alkali-removing residue was 2.5% by mass percentage; the drying temperature was 105℃. The dry basis composition of the caustic slag used, by mass percentage, includes: 70% CaCO3, 20% 3CaO·Al2O3·6H2O, 6% Ca(OH)2, 2% Na2O, and the remainder being trace impurities.
[0089] Step 2: Mix the dealkali residue with the composite modifier at high speed (1500 rpm) for 15 minutes to obtain the calcined raw material; The mass ratio of causticizing slag to composite modifier is 100:0.87; The preparation method of the composite modifier includes: mixing LiF, La(NO3)3·6H2O, CeO2 and Na2B4O7·10H2O uniformly in a mass ratio of 6:1.5:0.5:0.7; the particle size of CeO2 is in the nanometer range. Step 3: Perform microwave stepped calcination on the calcined raw material at a heating rate of 85℃ / min to obtain calcined clinker; Microwave stepped calcination treatment includes sequentially performing low-temperature dehydration and activation treatment, medium-temperature decomposition treatment, and heat preservation and homogenization treatment on the calcined raw materials. The microwave power for the low-temperature dehydration activation treatment was 7kW; the homogenization temperature for the low-temperature dehydration activation treatment was 500℃; and the homogenization time for the low-temperature dehydration activation treatment was 10min. The microwave power for the intermediate-temperature decomposition treatment was 11kW; the homogenization temperature for the intermediate-temperature decomposition treatment was 820℃; and the homogenization time for the intermediate-temperature decomposition treatment was 22min. The microwave power for the heat preservation and homogenization treatment was 6kW; the homogenization temperature for the heat preservation and homogenization treatment was 780℃; and the homogenization time for the heat preservation and homogenization treatment was 6min. Step 4: Rapidly cool the calcined clinker to obtain a calcium aluminate-calcium oxide composite material; The rapid cooling process includes cooling the calcined clinker to 180°C at a cooling rate of 110°C / min.
[0090] The obtained calcium aluminate-calcium oxide composite material, by mass percentage, contains: 85% CaO, 12% 3CaO·Al2O3, 0.3% Na2O residue, and the balance being SiO2, rare earth elements, borates, and trace impurities. The CaO activity in the calcium aluminate-calcium oxide composite material is 440 mL.
[0091] In addition, the calcium aluminate-calcium oxide composite material of this embodiment was also applied, specifically including: salt desalination causticization process and deep desilication process.
[0092] The application methods of salt removal and causticization processes include: With a CaO / Na2CO3 molar ratio of 1.1, calcium aluminate-calcium oxide composite material, ball-milled to a particle size of less than 45 μm, was mixed with seed mother liquor and reacted at 100℃ for 75 min. After the reaction, the mixture was separated by sedimentation to obtain causticizing liquid and residue.
[0093] Under these conditions, the causticization efficiency is 97% and the Al2O3 recovery rate is 93%.
[0094] Applications of deep desilication technology include: The calcium aluminate-calcium oxide composite material, which is ball-milled to a particle size of less than 45 μm, is mixed with the crude liquid at a CaO / SiO2 molar ratio of 3.0 and reacted at 105℃ for 60 min. The reaction product is then separated by sedimentation to obtain the refined liquid.
[0095] This process can achieve a desilication index of 0.96 and a SiO2 content of 0.07 g / L in semen.
[0096] Example 2 Example 2 provides a method for preparing calcium aluminate-calcium oxide composite material, comprising the following steps: Step 1: Dealkali treatment is performed on the causticizing slag to obtain dealkali-treated slag; The dealkali removal process includes the following steps: The causticized slag and water were mixed in a reaction vessel at a solid-liquid ratio of 1g:4mL and stirred for the first time to obtain a solid-liquid mixture. The stirring temperature for the first stirring was 80℃, the stirring time for the first stirring was 0.1h, and the stirring rate for the first stirring was 200r / min. A solid-liquid mixture is subjected to liquid-solid separation treatment to obtain a solid phase; The solid material was successively dried and ground to obtain alkali-removing residue with a particle size ≤75μm; the moisture content of the alkali-removing residue was 2.8% by mass percentage; the drying temperature was 105℃. In the embodiments of this application, the dry composition of the caustic slag used, by mass percentage, includes: 65% CaCO3, 23% 3CaO·Al2O3·6H2O, 3% Ca(OH)2, 1% Na2O, 1% SiO2, and the remainder being trace impurities.
[0097] Step 2: Mix the dealkali residue with the composite modifier at high speed (1500 rpm) for 15 minutes to obtain the calcined raw material; The mass ratio of causticizing slag to composite modifier is 100:0.65; The preparation method of the composite modifier includes: mixing LiF, La(NO3)3·6H2O, CeO2 and Na2B4O7·10H2O uniformly in a mass ratio of 3:1:2:0.5; the particle size of CeO2 is nanoscale; Step 3: Perform microwave stepped calcination on the calcined raw material at a heating rate of 80℃ / min to obtain calcined clinker; Microwave stepped calcination treatment includes sequentially performing low-temperature dehydration and activation treatment, medium-temperature decomposition treatment, and heat preservation and homogenization treatment on the calcined raw materials. The microwave power for the low-temperature dehydration activation treatment was 6kW; the homogenization temperature for the low-temperature dehydration activation treatment was 450℃; and the homogenization time for the low-temperature dehydration activation treatment was 12min. The microwave power for the intermediate-temperature decomposition treatment was 10kW; the homogenization temperature for the intermediate-temperature decomposition treatment was 780℃; and the homogenization time for the intermediate-temperature decomposition treatment was 25min. The microwave power for the heat preservation and homogenization treatment was 5kW; the homogenization temperature for the heat preservation and homogenization treatment was 750℃; and the homogenization time for the heat preservation and homogenization treatment was 8min. Step 4: Rapidly cool the calcined clinker to obtain a calcium aluminate-calcium oxide composite material; The rapid cooling process includes cooling the calcined clinker to 190°C at a cooling rate of 130°C / min.
[0098] The obtained calcium aluminate-calcium oxide composite material, by mass percentage, contains: 82.1% CaO, 10.3% 3CaO·Al2O3, 0.25% residual Na2O, and the balance being SiO2, rare earth elements, borates, and trace impurities. The CaO activity in the aforementioned calcium aluminate-calcium oxide composite material is 381 mL.
[0099] In addition, the calcium aluminate-calcium oxide composite material of this embodiment was also applied, specifically including: salt desalination causticization process and deep desilication process.
[0100] The application methods of salt removal and causticization processes include: The calcium aluminate-calcium oxide composite material, which has been ball-milled to a particle size of less than 45 μm, is mixed with the seed mother liquor at a CaO / Na2CO3 molar ratio of 1.05 and reacted at 95℃ for 90 min. After the reaction is completed, the causticizing liquid and residue are obtained by sedimentation separation.
[0101] Under these conditions, the causticization efficiency was 96.5%, and the Al2O3 recovery rate was 92.9%.
[0102] Applications of deep desilication technology include: The calcium aluminate-calcium oxide composite material, which has been ball-milled to a particle size of less than 45 μm, was mixed with the crude liquid at a CaO / SiO2 molar ratio of 2.8 and reacted at 100℃ for 60 min. The reaction product was then separated by sedimentation to obtain the refined liquid.
[0103] This process can achieve a desilication index of 0.96 and a SiO2 content of 0.079 g / L in semen.
[0104] Example 3 Example 3 provides a method for preparing calcium aluminate-calcium oxide composite material, comprising the following steps: Step 1: Dealkali treatment is performed on the causticizing slag to obtain dealkali-treated slag; The dealkali removal process includes the following steps: The causticized slag and water were mixed in a reaction vessel at a solid-liquid ratio of 1g:6mL and stirred for the first time to obtain a solid-liquid mixture. The stirring temperature for the first stirring was 90℃, the stirring time for the first stirring was 40min, and the stirring speed for the first stirring was 220r / min. A solid-liquid mixture is subjected to liquid-solid separation treatment to obtain a solid phase; The solid material was successively dried and ground to obtain alkali-removing residue with a particle size ≤88μm; the moisture content of the alkali-removing residue was 2.2% by mass percentage; the drying temperature was 105℃. The dry basis composition of the caustic slag used, by mass percentage, includes: 65% CaCO3, 20% 3CaO·Al2O3·6H2O, 8% Ca(OH)2, 3% Na2O, and the remainder being trace impurities.
[0105] Step 2: Mix the dealkali residue with the composite modifier at high speed (1500 rpm) for 15 minutes to obtain the calcined raw material; The mass ratio of causticizing slag to composite modifier is 100:1.3; The preparation method of the composite modifier includes: mixing LiF, La(NO3)3·6H2O, CeO2 and Na2B4O7·10H2O uniformly in a mass ratio of 6:3:2:2; the particle size of CeO2 is in the nanometer range; Step 3: Perform microwave stepped calcination on the calcined raw material at a heating rate of 110℃ / min to obtain calcined clinker; Microwave stepped calcination treatment includes sequentially performing low-temperature dehydration and activation treatment, medium-temperature decomposition treatment, and heat preservation and homogenization treatment on the calcined raw materials. The microwave power for the low-temperature dehydration activation treatment was 8kW; the homogenization temperature for the low-temperature dehydration activation treatment was 550℃; and the homogenization time for the low-temperature dehydration activation treatment was 8min. The microwave power for the intermediate-temperature decomposition treatment was 12kW; the homogenization temperature for the intermediate-temperature decomposition treatment was 850℃; and the homogenization time for the intermediate-temperature decomposition treatment was 20min. The microwave power for the heat preservation and homogenization treatment was 7kW; the homogenization temperature for the heat preservation and homogenization treatment was 800℃; and the homogenization time for the heat preservation and homogenization treatment was 5min. Step 4: Rapidly cool the calcined clinker to obtain a calcium aluminate-calcium oxide composite material; The rapid cooling process includes cooling the calcined clinker to 170°C at a cooling rate of 120°C / min.
[0106] The obtained calcium aluminate-calcium oxide composite material, by mass percentage, contains: 86% CaO, 12.5% 3CaO·Al2O3, 0.3% residual Na2O, and the balance being SiO2, rare earth elements, borates, and trace impurities. The CaO activity in the composite material is 420 mL.
[0107] In addition, the calcium aluminate-calcium oxide composite material of this embodiment was also applied, specifically including: salt desalination causticization process and deep desilication process.
[0108] The application methods of salt removal and causticization processes include: The calcium aluminate-calcium oxide composite material, which has been ball-milled to a particle size of less than 45 μm, is mixed with the seed mother liquor at a CaO / Na2CO3 molar ratio of 1.15 and reacted at 105℃ for 60 min. After the reaction is completed, the causticizing liquid and residue are obtained by sedimentation separation.
[0109] Under these conditions, the causticization efficiency is 98% and the Al2O3 recovery rate is 94%.
[0110] Applications of deep desilication technology include: With a CaO / SiO2 molar ratio of 3.2, calcium aluminate-calcium oxide composite material, which has been ball-milled to a particle size of less than 45 μm, is mixed with crude liquid and reacted at 110℃ for 60 min. The reaction product is then separated by sedimentation to obtain refined liquid.
[0111] This process can achieve a desilication index of 0.97 and a SiO2 content of 0.06 g / L in semen.
[0112] Example 4 Example 4 provides a method for preparing calcium aluminate-calcium oxide composite material, comprising the following steps: Step 1: Dealkali treatment is performed on the causticizing slag to obtain dealkali-treated slag; The dealkali removal process includes the following steps: The causticized slag and water were mixed in a reaction vessel at a solid-liquid ratio of 1g:5mL and stirred for the first time to obtain a solid-liquid mixture. The stirring temperature for the first stirring was 85℃, the stirring time for the first stirring was 35min, and the stirring speed for the first stirring was 200r / min. A solid-liquid mixture is subjected to liquid-solid separation treatment to obtain a solid phase; The solid material was successively dried and ground to obtain alkali-removing residue with a particle size ≤74μm; the moisture content of the alkali-removing residue was 2.4% by mass percentage; the drying temperature was 105℃. The dry basis composition of the caustic slag used, by mass percentage, includes: 68% CaCO3, 22% 3CaO·Al2O3·6H2O, 5% Ca(OH)2, 2.5% Na2O, and the remainder being trace impurities.
[0113] Step 2: Mix the dealkali residue with the composite modifier at high speed (1500 rpm) for 15 minutes to obtain the calcined raw material; The mass ratio of causticizing slag to composite modifier is 100:0.9; The preparation method of the composite modifier includes: mixing LiF, La(NO3)3·6H2O, CeO2 and Na2B4O7·10H2O in a mass ratio of 4.5:2:1:1.5; Step 3: Perform microwave stepped calcination on the calcined raw material at a heating rate of 120℃ / min to obtain calcined clinker; Microwave stepped calcination treatment includes sequentially performing low-temperature dehydration and activation treatment, medium-temperature decomposition treatment, and heat preservation and homogenization treatment on the calcined raw materials. The microwave power for the low-temperature dehydration activation treatment was 7kW; the homogenization temperature for the low-temperature dehydration activation treatment was 500℃; and the homogenization time for the low-temperature dehydration activation treatment was 10min. The microwave power for the intermediate-temperature decomposition treatment was 11kW; the homogenization temperature for the intermediate-temperature decomposition treatment was 800℃; and the homogenization time for the intermediate-temperature decomposition treatment was 23min. The microwave power for the heat preservation and homogenization treatment was 6kW; the homogenization temperature for the heat preservation and homogenization treatment was 780℃; and the homogenization time for the heat preservation and homogenization treatment was 7min. Step 4: Rapidly cool the calcined clinker to obtain a calcium aluminate-calcium oxide composite material; The rapid cooling process includes cooling the calcined clinker to 185°C at a cooling rate of 160°C / min.
[0114] The obtained calcium aluminate-calcium oxide composite material, by mass percentage, contains: 84% CaO, 10% 3CaO·Al2O3, 0.35% residual Na2O, and the balance being SiO2, rare earth elements, borates, and trace impurities. The CaO activity in the calcium aluminate-calcium oxide composite material is 405 mL.
[0115] In addition, the calcium aluminate-calcium oxide composite material of this embodiment was also applied, specifically including: salt desalination causticization process and deep desilication process.
[0116] The application methods of salt removal and causticization processes include: The calcium aluminate-calcium oxide composite material, which has been ball-milled to a particle size of less than 50 μm, is mixed with the seed mother liquor at a CaO / Na2CO3 molar ratio of 1.1 and reacted at 100℃ for 70 min. After the reaction is completed, the causticizing liquid and residue are obtained by sedimentation separation.
[0117] Under these conditions, the causticization efficiency is 97.5%, and the Al2O3 recovery rate is 93.5%.
[0118] Applications of deep desilication technology include: With a CaO / SiO2 molar ratio of 3.0, calcium aluminate-calcium oxide composite material that has been ball-milled to a particle size of less than 50 μm is mixed with crude liquid and reacted at 105℃ for 60 min. The reaction product is then separated by sedimentation to obtain refined liquid.
[0119] This process can achieve a desilication index of 0.96 and a SiO2 content of 0.07 g / L in semen.
[0120] Example 5 Example 5 provides a method for preparing calcium aluminate-calcium oxide composite material, comprising the following steps: Step 1: Dealkali treatment is performed on the causticizing slag to obtain dealkali-treated slag; The composition of the causticizing slag and the dealkali slag used are the same as those in Example 1, and will not be repeated here.
[0121] Step 2: Mix the dealkali residue with the composite modifier to obtain the calcined raw material; The mass ratio of causticizing slag to composite modifier is 100:0.7; The preparation method of the composite modifier includes: mixing LiF, La(NO3)3·6H2O, CeO2 and Na2B4O7·10H2O in a mass ratio of 4:1.5:0.8:0.7; Step 3: Perform microwave stepped calcination on the calcined raw material at a heating rate of 100℃ / min to obtain calcined clinker; Microwave stepped calcination treatment includes sequentially performing low-temperature dehydration and activation treatment, medium-temperature decomposition treatment, and heat preservation and homogenization treatment on the calcined raw materials. The microwave power for the low-temperature dehydration activation treatment was 7.5 kW; the homogenization temperature for the low-temperature dehydration activation treatment was 480 ℃; and the homogenization time for the low-temperature dehydration activation treatment was 11 min. The microwave power for the intermediate-temperature decomposition treatment was 11.5 kW; the homogenization temperature for the intermediate-temperature decomposition treatment was 810 ℃; and the homogenization time for the intermediate-temperature decomposition treatment was 22 min. The microwave power for the heat preservation and homogenization treatment was 6.5kW; the homogenization temperature for the heat preservation and homogenization treatment was 770℃; and the homogenization time for the heat preservation and homogenization treatment was 6.5min. Step 4: Rapidly cool the calcined clinker to obtain a calcium aluminate-calcium oxide composite material; The rapid cooling process includes cooling the calcined clinker to 195°C at a cooling rate of 180°C / min.
[0122] The obtained calcium aluminate-calcium oxide composite material, by mass percentage, contains: 85% CaO, 12% 3CaO·Al2O3, 0.3% residual Na2O, and the balance being SiO2, rare earth elements, borates, and trace impurities. The CaO activity in the composite material is 440 mL.
[0123] In addition, the calcium aluminate-calcium oxide composite material of this embodiment was also applied, specifically including: salt desalination causticization process and deep desilication process.
[0124] The application methods of salt removal and causticization processes include: The calcium aluminate-calcium oxide composite material, which has been ball-milled to a particle size of less than 53 μm, is mixed with the seed mother liquor at a CaO / Na2CO3 molar ratio of 1.08 and reacted at 102℃ for 80 min. After the reaction is completed, the causticizing liquid and residue are obtained by sedimentation separation.
[0125] Under these conditions, the causticization efficiency is 97.2%, and the Al2O3 recovery rate is >93.2%.
[0126] Applications of deep desilication technology include: The calcium aluminate-calcium oxide composite material, which has been ball-milled to a particle size of less than 53 μm, was mixed with the crude liquid at a CaO / SiO2 molar ratio of 2.9 and reacted at 108℃ for 60 min. The reaction product was then separated by sedimentation to obtain the refined liquid.
[0127] This process can achieve a desilication index of 0.965 and a SiO2 content of 0.065 g / L in the semen.
[0128] Comparative Example 1 Comparative Example 1 provides a method for preparing calcium aluminate-calcium oxide composite material, comprising the following steps: Step 1: Dealkali treatment is performed on the causticizing slag to obtain dealkali-treated slag; The dealkali removal process includes the following steps: The causticized slag and water were mixed in a reaction vessel at a solid-liquid ratio of 1g:5mL and stirred for the first time to obtain a solid-liquid mixture. The stirring temperature for the first stirring was 85℃, the stirring time for the first stirring was 35min, and the stirring speed for the first stirring was 200r / min. A solid-liquid mixture is subjected to liquid-solid separation treatment to obtain a solid phase (filter cake) and a filtrate; The solid material was successively dried and ground (ball milled) to obtain alkali-removing residue with a particle size ≤80μm; the moisture content of the alkali-removing residue was 2.5% by mass percentage; the drying temperature was 105℃. The dry basis composition of the caustic slag used, by mass percentage, includes: 70% CaCO3, 20% 3CaO·Al2O3·6H2O, 6% Ca(OH)2, 2% Na2O, 2% SiO2, and the remainder being trace impurities.
[0129] Step 2: Heat the dealkali residue in a rotary kiln to 1050℃ at a heating rate of 8℃ / min, and keep it at 1050℃ for 2.5h to obtain calcined clinker; Step 3: Cool the calcined clinker naturally to room temperature to obtain calcium aluminate-calcium oxide composite material.
[0130] The obtained calcium aluminate-calcium oxide composite material, by mass percentage, contains: 78% CaO, 11% 3CaO·Al2O3, 1.5% residual Na2O, and the balance being SiO2, rare earth elements, borates, and trace impurities. The CaO activity in the calcium aluminate-calcium oxide composite material is 240 mL.
[0131] In addition, the calcium aluminate-calcium oxide composite material of this comparative example was also applied in the following specific applications: salt desalination and causticizing processes, and deep desilication processes.
[0132] The application methods of salt removal and causticization processes include: With a CaO / Na2CO3 molar ratio of 1.1, calcium aluminate-calcium oxide composite material, ball-milled to a particle size of less than 45 μm, was mixed with seed mother liquor and reacted at 100℃ for 75 min. After the reaction, the mixture was separated by sedimentation to obtain causticizing liquid and residue.
[0133] Under these conditions, the causticization efficiency is 87%, and the Al2O3 recovery rate is 58%.
[0134] Applications of deep desilication technology include: With a CaO / SiO2 molar ratio of 3.0, calcium aluminate-calcium oxide composite material, which has been ball-milled to a particle size of less than 45 μm, is mixed with crude liquid and reacted at 105℃ for 60 min. The reaction product is then separated by sedimentation to obtain refined liquid.
[0135] The process achieves a desilication index of 0.85 and a SiO2 content of 0.15 g / L in the semen.
[0136] Comparative Example 2 Comparative Example 2 provides a method for preparing calcium aluminate-calcium oxide composite material, comprising the following steps: Step 1: Dealkali treatment is performed on the causticizing slag to obtain dealkali-treated slag; The dealkali removal process includes the following steps: The causticized slag and water were mixed in a reaction vessel at a solid-liquid ratio of 1g:5mL and stirred for the first time to obtain a solid-liquid mixture. The stirring temperature for the first stirring was 85℃, the stirring time for the first stirring was 35min, and the stirring speed for the first stirring was 200r / min. A solid-liquid mixture is subjected to liquid-solid separation treatment to obtain a solid phase (filter cake) and a filtrate; The solid material was successively dried and ground (ball milled) to obtain alkali-removing residue with a particle size ≤80μm; the moisture content of the alkali-removing residue was 2.5% by mass percentage; the drying temperature was 105℃. The dry basis composition of the caustic slag used, by mass percentage, includes: 70% CaCO3, 20% 3CaO·Al2O3·6H2O, 6% Ca(OH)2, 2% Na2O, 2% SiO2, and the remainder being trace impurities.
[0137] Step 2: Microwave calcination treatment of the dealkali residue is carried out at a heating rate of 85℃ / min to obtain calcined clinker; The microwave single-stage calcination treatment includes heating the dealkali residue to 850℃ at a microwave power of 10kW and holding it at 850℃ for 45 minutes. Step 3: Allow the calcined clinker to cool naturally to obtain a calcium aluminate-calcium oxide composite material.
[0138] The obtained calcium aluminate-calcium oxide composite material, by mass percentage, contains: 81% CaO, 12% 3CaO·Al2O3, 1.1% residual Na2O, and the balance being SiO2, rare earth elements, borates, and trace impurities. The CaO activity in the calcium aluminate-calcium oxide composite material is 300 mL.
[0139] In addition, the calcium aluminate-calcium oxide composite material of this comparative example was also applied in the following specific applications: salt desalination and causticizing processes, and deep desilication processes.
[0140] The application methods of salt removal and causticization processes include: With a CaO / Na2CO3 molar ratio of 1.1, calcium aluminate-calcium oxide composite material, ball-milled to a particle size of less than 45 μm, was mixed with seed mother liquor and reacted at 100℃ for 75 min. After the reaction, the mixture was separated by sedimentation to obtain causticizing liquid and residue.
[0141] Under these conditions, the causticization efficiency is 86%, and the Al2O3 recovery rate is 78%.
[0142] Applications of deep desilication technology include: With a CaO / SiO2 molar ratio of 3.0, calcium aluminate-calcium oxide composite material, which has been ball-milled to a particle size of less than 45 μm, is mixed with crude liquid and reacted at 105℃ for 60 min. The reaction product is then separated by sedimentation to obtain refined liquid.
[0143] This process can achieve a desilication index of 0.88 and a SiO2 content of 0.12 g / L in semen.
[0144] Comparative Example 3 Comparative Example 3 provides a method for preparing calcium aluminate-calcium oxide composite material, which differs from Example 1 in that no composite modifier is added.
[0145] The remaining steps and parameters are the same as in Example 1, and will not be repeated here.
[0146] The obtained calcium aluminate-calcium oxide composite material, by mass percentage, contains: 81% CaO, 11.5% 3CaO·Al2O3, 1.0% residual Na2O, and the balance being SiO2, rare earth elements, borates, and trace impurities. The CaO activity in the calcium aluminate-calcium oxide composite material is 320 mL.
[0147] In addition, the calcium aluminate-calcium oxide composite material of this comparative example was applied in two specific applications: salt removal causticization process and deep desilication process. The results of the salt removal causticization process were: causticization efficiency of 89% and Al2O3 recovery rate of 82%. The results of the deep desilication process were: desilication index of 0.90 and SiO2 content in the concentrate of 0.105 g / L.
[0148] Comparative Example 4 Comparative Example 4 provides a method for preparing a calcium aluminate-calcium oxide composite material, which differs from Example 1 in that the composite modifier added is different. The composite modifier added in Comparative Example 4 is a mixture of La(NO3)3·6H2O, CeO2, and Na2B4O7·10H2O in a mass ratio of 1.5:0.5:0.7.
[0149] The remaining steps and parameters are the same as in Example 1, and will not be repeated here.
[0150] The obtained calcium aluminate-calcium oxide composite material, by mass percentage, contains: 81.5% CaO, 11% 3CaO·Al2O3, 0.65% residual Na2O, and the balance being SiO2, rare earth elements, borates, and trace impurities. The CaO activity in the calcium aluminate-calcium oxide composite material is 355 mL.
[0151] In addition, the calcium aluminate-calcium oxide composite material of this comparative example was applied in two specific applications: salt removal causticization process and deep desilication process. The results of the salt removal causticization process were: causticization efficiency of 91% and Al2O3 recovery rate of 86%. The results of the deep desilication process were: desilication index of 0.91 and SiO2 content in the concentrate of 0.098 g / L.
[0152] Comparative Example 5 Comparative Example 5 provides a method for preparing a calcium aluminate-calcium oxide composite material, which differs from Example 1 in that the composite modifier added is different. The composite modifier added in Comparative Example 5 is a mixture of LiF, CeO2, and Na2B4O7·10H2O in a mass ratio of 6:0.5:0.7.
[0153] The remaining steps and parameters are the same as in Example 1, and will not be repeated here.
[0154] The obtained calcium aluminate-calcium oxide composite material, by mass percentage, contains: 82% CaO, 11% 3CaO·Al2O3, 0.90% residual Na2O, and the balance being SiO2, rare earth elements, borates, and trace impurities. The CaO activity in the calcium aluminate-calcium oxide composite material is 350 mL.
[0155] In addition, the calcium aluminate-calcium oxide composite material of this comparative example was applied in two specific applications: salt removal causticization process and deep desilication process. The results of the salt removal causticization process were: causticization efficiency of 90% and Al2O3 recovery rate of 83%. The results of the deep desilication process were: desilication index of 0.9 and SiO2 content in the concentrate of 0.105 g / L.
[0156] Comparative Example 6 Comparative Example 6 provides a method for preparing a calcium aluminate-calcium oxide composite material, which differs from Example 1 in that the composite modifier added is different. The composite modifier added in Comparative Example 6 is a mixture of LiF, La(NO3)3·6H2O, and Na2B4O7·10H2O in a mass ratio of 6:1.5:0.7.
[0157] The remaining steps and parameters are the same as in Example 1, and will not be repeated here.
[0158] The obtained calcium aluminate-calcium oxide composite material, by mass percentage, contains: 83% CaO, 11.8% 3CaO·Al2O3, 0.55% residual Na2O, and the balance being SiO2, rare earth elements, borates, and trace impurities. The CaO activity in the calcium aluminate-calcium oxide composite material is 390 mL.
[0159] In addition, the calcium aluminate-calcium oxide composite material of this comparative example was applied in two specific applications: salt removal causticization process and deep desilication process. The results of the salt removal causticization process were: causticization efficiency of 93% and Al2O3 recovery rate of 89.5%. The results of the deep desilication process were: desilication index of 0.93 and SiO2 content in the concentrate of 0.088 g / L.
[0160] Comparative Example 7 Comparative Example 7 provides a method for preparing a calcium aluminate-calcium oxide composite material, which differs from Example 1 in that the composite modifier added is different. The composite modifier added in Comparative Example 7 is a mixture of LiF, La(NO3)3·6H2O and CeO2 in a mass ratio of 6:1.5:0.5.
[0161] The remaining steps and parameters are the same as in Example 1, and will not be repeated here.
[0162] The obtained calcium aluminate-calcium oxide composite material, by mass percentage, contains: 82.5% CaO, 11.2% 3CaO·Al2O3, 0.8% residual Na2O, and the balance being SiO2, rare earth elements, borates, and trace impurities. The CaO activity in the calcium aluminate-calcium oxide composite material is 355 mL.
[0163] In addition, the calcium aluminate-calcium oxide composite material of this comparative example was applied in two specific applications: salt removal causticization process and deep desilication process. The results of the salt removal causticization process were: causticization efficiency of 89.5% and Al2O3 recovery rate of 84%. The results of the deep desilication process were: desilication index of 0.905 and SiO2 content in the concentrate of 0.102 g / L.
[0164] Comparative Example 8 Comparative Example 8 provides a method for preparing a calcium aluminate-calcium oxide composite material, which differs from Example 1 in that it uses a natural cooling method. The composition and amount of the composite agent added in Comparative Example 8 are exactly the same as those in Example 1.
[0165] The remaining steps and parameters are the same as in Example 1, and will not be repeated here.
[0166] The obtained calcium aluminate-calcium oxide composite material, by mass percentage, contains: 84% CaO, 11.5% 3CaO·Al2O3, 0.65% residual Na2O, and the balance being SiO2, rare earth elements, borates, and trace impurities. The CaO activity in the calcium aluminate-calcium oxide composite material is 340 mL.
[0167] In addition, the calcium aluminate-calcium oxide composite material of this comparative example was applied in two specific applications: salt removal causticization process and deep desilication process. The results of the salt removal causticization process were: causticization efficiency of 88.5% and Al2O3 recovery rate of 82%. The results of the deep desilication process were: desilication index of 0.895 and SiO2 content in the concentrate of 0.108 g / L.
[0168] Comparative Example 9 Comparative Example 9 provides a method for preparing a calcium aluminate-calcium oxide composite material, which differs from Example 1 in that the content of the composite modifier is different. In Comparative Example 9, the mass ratio of causticizing slag to composite modifier is 100:1.6.
[0169] The remaining steps and parameters are the same as in Example 1, and will not be repeated here.
[0170] The obtained calcium aluminate-calcium oxide composite material, by mass percentage, contains: 81% CaO, 10.5% 3CaO·Al2O3, 0.25% residual Na2O, and the balance being SiO2, rare earth elements, borates, and trace impurities. The CaO activity in the calcium aluminate-calcium oxide composite material is 390 mL.
[0171] In addition, the calcium aluminate-calcium oxide composite material of this comparative example was applied in two specific applications: salt removal causticization process and deep desilication process. The results of the salt removal causticization process were: causticization efficiency of 94% and Al2O3 recovery rate of 90.5%. The results of the deep desilication process were: desilication index of 0.94 and SiO2 content in the concentrate of 0.082 g / L.
[0172] Analysis of experimental results: Comparing Example 1 and Comparative Example 1, it can be seen that Comparative Example 1 did not add a composite modifier; and it used a traditional rotary kiln calcination process instead of microwave stepped calcination. It is evident that the product obtained by the method provided in this application has better application effects. The activity is increased by approximately 83% (from 240 mL to 440 mL), the CaO content increases from 78% to 85%, the Na2O residue decreases by approximately 80%, the Al2O3 recovery rate increases by approximately 60%, and energy consumption is significantly reduced.
[0173] Comparing Example 1 and Comparative Example 2, it can be seen that Comparative Example 2 did not add the composite modifier; and it used microwave single calcination treatment instead of microwave stepped calcination treatment, demonstrating the significant advantage of the synergistic effect of the composite modifier and microwave stepped calcination in this application. Compared with Comparative Example 2, Example 1 showed an increase in activity of approximately 47% (from 300 mL to 440 mL), an increase in CaO content of 81% to 85%, a decrease in Na2O residue of 1.1% to 0.3%, an increase in Al2O3 recovery rate of approximately 16%, and a decrease in energy consumption of approximately 15%.
[0174] Comparing Example 1 with Comparative Examples 3 and 9, it can be seen that the content of the added composite modifier has a significant impact on the residual Na2O, the effective ratio of free CaO to calcium aluminate, the product activity, and the recycling efficiency. When the amount of modifier added is insufficient (Comparative Example 3, no modifier), the in-situ sodium fixation effect is lost, the residual Na2O is as high as 1.0%, and the calcium carbonate decomposition is incomplete, the grains are easily coarsened, the activity is only 320 mL, and the recycling causticization and desilication indicators are all reduced. When the amount of modifier added is too high (Comparative Example 9, 100:1.6), although Na2O is further reduced to 0.25%, the excessive modifier dilutes CaO and 3CaO. The presence of an effective Al2O3 phase and excessive encapsulation of active crystal grains by the borate glass phase leads to a decrease in product activity and recycling efficiency, while significantly increasing raw material costs. Therefore, the amount of modifier added needs to be controlled within a reasonable range of 100:(0.4~1.3).
[0175] Comparing Example 1 and Comparative Examples 4-7, it can be seen that each component in the added composite modifier has an indispensable synergistic effect on the in-situ sodium fixation depth, calcium carbonate decomposition, crystal form stability and product activity. Among them, the lithium source is used to disrupt the CaCO3 crystal lattice, reduce the decomposition activation energy, promote low-temperature and efficient decomposition, and buffer the migration and volatilization of sodium ions. Its absence significantly reduces CaO content and activity (Comparative Example 4, activity 355 mL). The lanthanum source acts as the main lattice doping cation, stably locking sodium ions in the interstitial spaces of the calcium aluminate lattice, and is the core component for achieving deep in-situ sodium fixation. Its absence significantly increases Na2O residue (Comparative Example 5, 0.9%). The cerium source is used for synergistic catalytic activation, assisting in grain refinement, and enhancing crystal stability. It works synergistically with the lanthanum source to improve the sodium fixation effect. Its absence slightly reduces both activity and sodium fixation capacity (Comparative Example 6, activity 390 mL). The boron source is used to form a boron-oxygen liquid phase at low temperature to capture free sodium ions, and also acts as a liquid-phase flux to improve the uniformity of modifier dispersion. Its absence causes the low-temperature sodium capture process to fail, and Na2O residue significantly increases (Comparative Example 7, 0.8%). Therefore, all four components are indispensable, and their synergistic effect achieves a triple sodium fixation and activation effect through liquid-phase capture, lattice doping, and surface passivation.
[0176] Meanwhile, comparing Example 1 and Comparative Example 8, it can be seen that rapid cooling at 80℃ / min~180℃ / min is the key process for locking the high-temperature active crystal form and preventing sodium ion desorption and precipitation. Natural cooling will cause the crystal grains to recrystallize and coarsen, the activity will drop sharply to 340mL, and the solidified sodium will be redeprecipitated as soluble sodium salt, and the Na2O residue will increase to 0.65%, which cannot meet the requirements for low sodium and high activity recycling.
[0177] In summary, this application provides a calcium aluminate-calcium oxide composite material, its preparation method, and its application. The residual Na2O content in this calcium aluminate-calcium oxide composite material is less than 0.5%, effectively preventing the cyclic enrichment of sodium elements during the recycling of the composite material in alumina production, thus ensuring system operational stability. Simultaneously, it achieves synergistic and efficient recovery of CaO and Al2O3, improving resource utilization efficiency. The preparation method of the calcium aluminate-calcium oxide composite material involves dealkalizing the causticizing slag, introducing a composite modifier containing lithium, lanthanum, cerium, and boron sources, followed by microwave stepped calcination and rapid cooling to finally obtain the calcium aluminate-calcium oxide composite material. This method has the following beneficial effects: First, dealkalizing the causticizing slag effectively reduces the content of soluble sodium salts; during the subsequent microwave stepped calcination process, the dealkalized slag and the composite modifier synergistically exert an in-situ solidification effect, further inhibiting the cyclic enrichment of Na2O in the alumina production system. Secondly, in the composite modifier, the lithium and boron sources work synergistically to significantly reduce the activation energy of CaCO3 decomposition and promote efficient low-temperature reactions; the lanthanum and cerium sources work synergistically to effectively inhibit the sintering and grain coarsening of 3CaO·Al2O3 at high temperatures, stabilize its active crystal form, refine the product grains, and prevent calcium aluminate from passivating or agglomerating due to overheating; simultaneously, multiple modifying components work together to promote in-situ solidification of Na2O, reduce Na2O residue in the product, meet recycling requirements, and achieve efficient synergistic recovery of CaO and Al2O3. The obtained calcium aluminate-calcium oxide composite can be directly recycled for the desalination and causticization or deep desilication process in alumina production; in the causticization process, the causticization efficiency is >96%, and the Al2O3 recovery rate is >92%; in the desilication process, the desilication index is >0.95, and the refined solution SiO2 is <0.08 g / L. Compared to existing technologies that only recover CaO, this application achieves an Al2O3 recovery rate of >92% and a lime utilization rate of >95%, and constructs a closed-loop recycling system of "causticizing slag → composite modification → microwave calcination → reuse → new causticizing slag → recalcination". This process fully utilizes the volumetric and selective heating characteristics of microwave heating, combined with a stepped temperature control strategy, to reduce energy consumption while avoiding over-burning of materials, ultimately obtaining a highly active, low-alkali-residue calcium aluminate-calcium oxide composite material, fully meeting the technical requirements of modern clean, efficient, and sustainable alumina production. This application achieves efficient and simultaneous recovery of aluminum and calcium resources from the causticizing slag through precise control of the calcination process, preparing a high-performance calcium aluminate-calcium oxide composite material. This effectively solves the problems of resource waste, high energy consumption, poor product performance, and low solid waste utilization rate in existing technologies, realizing high-value resource utilization of industrial solid waste, reducing production costs, and balancing economic and ecological benefits.
[0178] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed in this application.
Claims
1. A calcium aluminate-calcium oxide composite material, characterized in that, The composition of the calcium aluminate-calcium oxide composite material, by mass percentage, includes: CaO: ≥82%, 3CaO·Al2O3: ≥10%, Na2O: <0.5%, and the remainder being impurities; The activity of CaO in the calcium aluminate-calcium oxide composite is >380 mL.
2. A method for preparing the calcium aluminate-calcium oxide composite material as described in claim 1, characterized in that, Includes the following steps: The causticizing slag is subjected to dealkali treatment to obtain dealkali-reduced slag; The dealkali-removed residue is mixed with a composite modifier to obtain a calcined raw material; The calcined raw material is subjected to microwave step-calcination treatment to obtain calcined clinker; and, The calcined clinker was subjected to rapid cooling treatment to obtain the calcium aluminate-calcium oxide composite material; The composite modifier includes lithium source, lanthanum source, cerium source and boron source.
3. The method for preparing calcium aluminate-calcium oxide composite material according to claim 2, characterized in that, The mass ratio of the causticizing slag to the composite modifier is 100:(0.4~1.3); and / or, In the composite modifier, the mass ratio of the lithium source, the lanthanum source, the cerium source, and the boron source is (2~6):(1~3):(0.5~2):(0.5~2).
4. The method for preparing calcium aluminate-calcium oxide composite material according to claim 3, characterized in that, The lithium source includes LiF; and / or, The lanthanum source includes La(NO3)3·6H2O; and / or, The cerium source includes CeO2; and / or, The boron source includes Na2B4O7·10H2O.
5. The method for preparing calcium aluminate-calcium oxide composite material according to claim 2, characterized in that, The microwave stepped calcination process includes sequentially subjecting the calcined raw materials to low-temperature dehydration and activation treatment, medium-temperature decomposition treatment, and heat preservation and homogenization treatment.
6. The method for preparing calcium aluminate-calcium oxide composite material according to claim 5, characterized in that, The microwave power for the low-temperature dehydration and activation treatment is 6kW~8kW; and / or, The homogenization temperature for the low-temperature dehydration and activation treatment is 450℃~550℃; and / or, The homogenization time for the low-temperature dehydration and activation treatment is 8 min to 12 min; and / or, The microwave power for the intermediate-temperature decomposition process is 10kW~12kW; and / or, The homogenization temperature of the mesophilic decomposition treatment is 780℃~850℃; and / or, The homogenization time for the mesophilic decomposition treatment is 20 min to 25 min; and / or, The microwave power for the heat preservation and homogenization treatment is 5kW~7kW; and / or, The homogenization temperature of the heat preservation treatment is 750℃~800℃; and / or, The homogenization time for the heat preservation treatment is 5 min to 8 min.
7. The method for preparing calcium aluminate-calcium oxide composite material according to claim 2, characterized in that, The dealkali removal treatment includes the following steps: The causticized residue is mixed with water and stirred for the first time to obtain a solid-liquid mixture; The solid-liquid mixture is subjected to liquid-solid separation treatment to obtain a solid phase; and, The solid phase is dried to obtain the dealkali residue.
8. The method for preparing calcium aluminate-calcium oxide composite material according to claim 7, characterized in that, The stirring temperature of the first stirrer is 80℃~90℃; and / or, The stirring time for the first stirring is 0.1 h to 1 h; and / or, The solid-liquid ratio of the causticized slag to water is 1 g:(2~6) mL; and / or, The drying process is performed at a temperature of 100℃~105℃; and / or, The moisture content of the dealkali removal residue is <3% by mass percentage; and / or, The particle size of the dealkali-removing residue is ≤127μm.
9. The method for preparing calcium aluminate-calcium oxide composite material according to any one of claims 2 to 8, characterized in that, The rapid cooling process includes cooling the calcined clinker to ≤200℃ at a cooling rate of 80℃ / min to 180℃ / min.
10. An application of the calcium aluminate-calcium oxide composite material according to claim 1, characterized in that, The calcium aluminate-calcium oxide composite material is used in salt desalination and causticizing processes and deep desilication processes.